Model Differentiated Learning in 21st Century Education: A Systematic Review of Strategies, Results, And Challenges - Silmi, Thoriq Aji; Lubis, Ardiansyah; Maulidi, Achmad (Fakultas Tarbiyah - Universitas Nahdlatul Ulama Sunan Giri, 2025)
Differentiated learning is a pedagogical approach that recognizes the diversity of students in terms of readiness, interests, and learning styles. This study aims to analyse the implementation, outcomes, and challenges of differentiated learning in 21st-century education. This study uses a systematic literature review method, which evaluates 22 selected articles from the Scopus and Google Scholar databases. The findings reveal that differentiated learning is effective in enhancing student engagement, material comprehension, and social skills through the adaptation of content, processes, products, and learning environments. However, its implementation faces challenges such as time management, limited human resources, and perceptions of inequity among students. Addressing these challenges requires enhancing teacher competence, providing adequate support from the education system, and implementing more effective classroom management. This study contributes by offering insights into differentiated learning practices and strategies relevant to the Merdeka Curriculum era and humanistic education.